1998
DOI: 10.1016/s0092-8674(00)81750-x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid A Acylation and Bacterial Resistance against Vertebrate Antimicrobial Peptides

Abstract: The Salmonellae PhoP-PhoQ virulence regulators induce resistance to host cationic antimicrobial peptides (CAMP) after infection of vertebrate tissues, and Mg2+ or Ca2+ limitation. The PhoP-PhoQ activated gene, pagP, was identified as important to inducible CAMP resistance and increased acylation of lipid A, the major component of the outer leaflet of the outer membrane. pagP mutants demonstrated increased outer membrane permeability in response to CAMP, supporting the hypothesis that increased lipid A acylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
553
1
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 586 publications
(569 citation statements)
references
References 45 publications
12
553
1
3
Order By: Relevance
“…Chemical modification of the arginine residues with BAD not only inhibited the antimicrobial activity of granulysin, but also interfered with the protein interaction with the bacterial cell wall or membrane. Previous studies indicate the role of the negatively charged bacterial cell membrane with cationic antimicrobial peptides (19). Taken together, these data indicate that ionic interactions between granulysin and bacterial membranes are required for optimal antimicrobial activity.…”
Section: Discussionsupporting
confidence: 62%
“…Chemical modification of the arginine residues with BAD not only inhibited the antimicrobial activity of granulysin, but also interfered with the protein interaction with the bacterial cell wall or membrane. Previous studies indicate the role of the negatively charged bacterial cell membrane with cationic antimicrobial peptides (19). Taken together, these data indicate that ionic interactions between granulysin and bacterial membranes are required for optimal antimicrobial activity.…”
Section: Discussionsupporting
confidence: 62%
“…PhoP orthologues regulate expression of genes essential for virulence and magnesium acquisition in several Gram-negative bacteria [14,20,11]. Some of the PhoP-induced enzymes promote increased bacterial resistance to antimicrobial peptides, a key component of host's innate immunity [10,17,21,22]. For example, PhoP-activated LPS modifications, including the addition of aminoarabinose and palmitate to lipid A, promote resistance to the antibiotic polymyxin and other cationic antimicrobial peptides [10,21,23].…”
Section: Quantitative Proteomic Analysis Defined P Aeruginosa Virulementioning
confidence: 99%
“…It was recently shown that treating Escherichia coli with EDTA leads to activation of PagP via a membrane perturbation mechanism (25). Palmitoylation of lipid A leads to an increased resistance of the bacterium to cationic antimicrobial peptides (20). Furthermore, palmitoylated LPS is attenuated for signaling through TLR4/MD-2 (24).…”
mentioning
confidence: 99%